2000
DOI: 10.1051/animres:2000111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dehydration on ruminal degradability of lucerne

Abstract: -The effects of industrial dehydration and a subsequent compression at high pressures on rumen degradability of lucerne were determined in 3 samples obtained at harvest or after the process of dehydration and compression of this forage. Rumen degradability of dry matter (DM) and nitrogen (N) was determined by the nylon bag technique in 3 ruminally cannulated wethers. Dehydration reduced effective DM degradability (from 63.4 to 59.4%), which was associated with an increase of both the rumen undegradable fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
2
6
1
Order By: Relevance
“…Mean values and standard error of k p values used to establish the ED estimates were 0.0226 ± 0.0021 (h -1 ). These values agree with those proposed by the AFRC [1] as a function of the intake level and they are very close to those obtained in similar conditions for dehydrated lucerne by Repetto et al [26].…”
Section: Ruminal Degradabilitysupporting
confidence: 92%
“…Mean values and standard error of k p values used to establish the ED estimates were 0.0226 ± 0.0021 (h -1 ). These values agree with those proposed by the AFRC [1] as a function of the intake level and they are very close to those obtained in similar conditions for dehydrated lucerne by Repetto et al [26].…”
Section: Ruminal Degradabilitysupporting
confidence: 92%
“…In particular, Hristov (1998) using the in sacco method on three steers, found an effective digestibility of CP of fresh alfalfa of 66.5% after 72h of incubation. In the same way, Repetto et al (2000) using an in sacco method on wethers within 72h of incubation found a percentage of protein degradability of 82%. Our values have to take into account the low incubation time (48h) and the use of faecal inoculum.…”
Section: Resultsmentioning
confidence: 69%
“…Dehydration of lucerne leads to an increase in the proportions of ADIN and specially NDIN and to a decrease in CP solubility [13]. Therefore, the high variability observed for the proportion of NDIN (CV = 26.3%) or the values of CP solubility (CV = 16.4%) will be related with the intensity of heating effects derived from the forage management and industrial treatments employed for the different plants.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the ED of all samples, between both incubation series of the studied sample, the rate constant describing the passage from the rumen of dietary particles (k p ) was determined for the dehydrated lucerne included in the diet, which had been chopped at 6-8 cm and marked with Ytterbium (Yb) by immersion [6], at 10 mg Yb·g -1 of feed. The Rumen degradation of dehydrated lucerne 29 procedure of this determination and the resultant k p values (2.28 ± 0.22%·h -1 ) has been previously published [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation